Care of gastrointestinal problems in the older adult - Meiner, Sue (Springer series on geriatric nursing., 2004)
Annotation This book provides nurses with practical information on the most frequently encountered gastrointestinal disorders and problems found in the elderly. It was developed to provide greater depth of information than can be found in general nursing textbooks, and to tailor this information to the special needs of the elderly. Each chapter includes a definition of the condition, followed by its cause, normal and abnormal physiology, nursing care with attention to nursing diagnoses, interventions, medications, and alternative therapies (where appropriate).